2022
DOI: 10.3390/cancers14041040
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the First Year of Follow-Up in a Randomized Multicenter Trial Assessing the Role of Imaging after Radical Surgery of Stage IIB-C and III Cutaneous Melanoma (TRIM Study)

Abstract: The benefit of imaging in the follow-up setting for high-risk melanoma patients is uncertain, and even less is known about the impact of intensive follow-up on the patient´s quality of life. In 2017, a Swedish prospective randomized multicenter study started, in which high-risk melanoma patients are randomly assigned 1:1 to follow-up by physical examinations +/− whole-body imaging. The first-year examinations are scheduled at 0, 6 and 12 months. The aim of this study was to investigate whether the patients´ he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Fewer blood tests and less imaging did not seem to have a negative impact on HRQoL or emotional well-being in most included articles 8 , 29 , 36 , 44 , 45 , 48 . One study 42 comparing conventional hospital follow-up with virtually no follow-up (physical examination every 5 years) found that HRQoL slightly favoured a more intensive approach.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Fewer blood tests and less imaging did not seem to have a negative impact on HRQoL or emotional well-being in most included articles 8 , 29 , 36 , 44 , 45 , 48 . One study 42 comparing conventional hospital follow-up with virtually no follow-up (physical examination every 5 years) found that HRQoL slightly favoured a more intensive approach.…”
Section: Discussionmentioning
confidence: 84%
“…Four studies, all RCTs, were included with a total of 784 patients in follow-up for melanoma. Sample size ranged from 100 to 297 patients 20 , 29 , 45 , 48 . Three studies were at low risk of bias, and none showed a significant difference in terms of HRQoL, psychological well-being, and patient satisfaction with different follow-up approaches.…”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation